2013
DOI: 10.1007/s10815-013-0100-4
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst expansion score and trophectoderm morphology strongly predict successful clinical pregnancy and live birth following elective single embryo blastocyst transfer (eSET): a national study

Abstract: Better trophectoderm morphology, younger patient age and further blastocyst progression all result in higher clinical pregnancy and live birth rates. Therefore, trophectoderm morphology and blastocyst stage should preferentially be used as the most important factors in choosing the best embryo for transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
60
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 23 publications
8
60
1
1
Order By: Relevance
“…We also found that blocking autophagy or PARylation increased apoptosis and decreased the total cell number in porcine IVP embryos, indicating that inhibiting either function during development can result in poor‐quality blastocysts. This phenotype is consistent with the observed defects in blastocyst development following treatment with 3ABA or 3MA, especially in blastocyst expansion, which is required for the proper development of the inner cell mass and trophectoderm (Thompson et al, ). These pro‐apoptotic outcomes might be accelerated by the accumulation of ubiquitinated substrates, such as misfolded or aggregated proteins and deformed organelles, as occurs in autophagy‐deficient mice (Moscat and Diaz‐Meco, ; Lippai and Lőw, ).…”
Section: Discussionsupporting
confidence: 87%
“…We also found that blocking autophagy or PARylation increased apoptosis and decreased the total cell number in porcine IVP embryos, indicating that inhibiting either function during development can result in poor‐quality blastocysts. This phenotype is consistent with the observed defects in blastocyst development following treatment with 3ABA or 3MA, especially in blastocyst expansion, which is required for the proper development of the inner cell mass and trophectoderm (Thompson et al, ). These pro‐apoptotic outcomes might be accelerated by the accumulation of ubiquitinated substrates, such as misfolded or aggregated proteins and deformed organelles, as occurs in autophagy‐deficient mice (Moscat and Diaz‐Meco, ; Lippai and Lőw, ).…”
Section: Discussionsupporting
confidence: 87%
“…Numerous studies have shown that pregnancy rates are comparable with eSET and DET in favorable prognosis women (14, 3437). Although the likelihood of clinical pregnancy and livebirth was greatest with DET, it should be noted that this observation includes preterm twin livebirths and their associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies suggest that trophectoderm is the more important of the two (2326). By contrast, a study by Van den Abbdeel et al, (27), found that blastocyst expansion, and both trophectoderm and inner cell mass are important for predicting pregnancy but that poor quality inner cell mass also predicts an increase in miscarriage rate.…”
Section: Discussionmentioning
confidence: 99%